Crystallographic and mass spectrometric analyses of a tandem GNAT protein from the clavulanic acid biosynthesis pathway. - Iqbal, A; Arunlanantham, H; Brown, T; Chowdhury, R; Clifton, I; Kershaw, N; Hewitson, K; McDonough, M; Schofield, C (2010)
(3R,5R)-Clavulanic acid (CA) is a clinically important inhibitor of Class A beta-lactamases. Sequence comparisons suggest that orf14 of the clavulanic acid biosynthesis gene cluster encodes for an acetyl transferase (CBG). Crystallographic studies reveal CBG to be a member of the emerging structural subfamily of tandem Gcn5-related acetyl transferase (GNAT) proteins. Two crystal forms (C2 and P2(1) space groups) of CBG were obtained; in both forms one molecule of acetyl-CoA (AcCoA) was bound to the N-terminal GNAT domain, with the C-terminal domain being unoccupied by a ligand. Mass spectrometric analyzes on CBG demonstrate that, in addition to one strongly bound AcCoA molecule, a second acyl-CoA molecule can bind to CBG. Succinyl-CoA and myristoyl-CoA displayed the strongest binding to the "second" CoA binding site, which is likely in the C-terminal GNAT domain. Analysis of the CBG structures, together with those of other tandem GNAT proteins, suggest that the AcCoA in the N-terminal GNAT domain plays a structural role whereas the C-terminal domain is more likely to be directly involved in acetyl transfer. The available crystallographic and mass spectrometric evidence suggests that binding of the second acyl-CoA occurs preferentially to monomeric rather than dimeric CBG. The N-terminal AcCoA binding site and the proposed C-terminal acyl-CoA binding site of CBG are compared with acyl-CoA binding sites of other tandem and single domain GNAT proteins.